PENGEMBANGAN MEDIA PEMBELAJARAN APLIKASI E-LES BERBASIS ANDROID PADA MATERI PERDAGANGAN INTERNASIONAL KELAS XI IPS SMA BRAWIJAYA SMART SCHOOL - Muhammad Rudy Alamsyah; Lisa Rokhmani; Muhammad Rudy Alamsyah (Universitas Negeri Malang, 2024)
Teachers have an important role in the learning process. The teacher is the key determinant of student success in achieving learning goals. To be able to improve the quality of learning, teachers must be able to choose the right learning methods and media so that students can understand the material presented. One way to make teaching and learning activities fun is to use multimedia learning media. The main objective of this research is to develop android-based learning media on class XI international trade material. The research was conducted at SMA Brawjaya Smart School. The research method used is research and development by following the steps of Borg and Gall. The results of the research conducted show that the media is in the very good category and the learning media is very suitable for use as a learning tool and learning media can also be used as a source of independent learning for students.